The Effectiveness of Using Assemblr Edu Application Media Based on AR (Augmented Reality) on Understanding the Concept of Elementary School Geomatry 3D - Suaib, Muhammad; Sutriyani, Wulan (Indonesian Journal of Education and Mathematical Science, 2024)
The purpose of the following research is to understand the effectiveness of the use of AR-based assemblr edu (augmented reality) applications applied to students in elementary school space building material. To understand the weight that students get before and after the assemblr edu application media is applied to learning. The following research uses an experimental quantitative approach method through the One Group Pretest Posttest Design design. The results of research using the assemblr edu application have an effective impact on understanding the concept of building elementary school space. The average score of students increased from 49 to 72. Statistical analysis with the SPSS version 25 application obtained the average value of the N-Gain score reached 0.74 which indicates a high category. While the significance data shows 0.000 (2-tailed) (0.000), the t-count value is 43.214 while the t-tabel is 21.788. The increase in the weight of the pretest and posttest understanding of the concept of building space is 0.88211 and is included in the high improvement category. The ES weight is 2.110 which is categorized as "high". Based on the existing requirements, the ES weight shows that the use of AR-based assemblr edu application media (Augmented Reality) is effective